VET Research Report 2009 : ReferNet-Research Report Germany - Hippach-Schneider, Ute [Herausgeber]; Toth, Bernadette [Herausgeber]; Berger, Susanne [Mitarbeiter]; Bohlinger, Sandra [Mitarbeiter]; Frommberger, Dietmar [Mitarbeiter]; Pilz, Matthias [Mitarbeiter]; Wilkens, Ingrid [Mitarbeiter] (Bundesinstitut für Berufsbildung, 2010)
"What is occupying the 'vocational education and training researchers' of a country? Is there any research of note? Which topics are being investigated and processed? Which relevant issues and material results are emerging? The answers to these questions enable a distinct insight to be obtained into a state's VET system by revealing focal points where 'construction works' are ongoing. Furthermore research is an indicator for the relevance of VET in a country. In 2009, an attempt was undertaken in all countries represented in ReferNet to respond to these questions via four main areas of content focus. 'Benefits of VET' and 'Mobility and migration' are common topics for all. Due to the fact that there are a large number of current issues of completely differing degrees of relevance within the member states, the national coordinators were given the freedom to decide on two further topics. Germany opted for the topics 'Effectiveness and quality assurance' and 'Transitions'." (Hrsg., BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; S System beruflicher Bildung; I 2.1 Deutschland; Berufsbildungsforschung; Berufsbildung; Kosten-Nutzen-Analyse; Bildungsertrag; Berufliche Mobilität; Migrant; Bildungschancengleichheit; Qualitätskontrolle; Berufseinmündung; Erste Schwelle; Zweite Schwelle; Bundesrepublik Deutschland